Membangun Etos Kerja Islami melalui Penerapan Akhlaq dan Hukum Islam - wulandari, septiayu; Yudianto, Ahmad (Tasyri' : Jurnal Muamalah dan Ekonomi Syariah, 2023)
Building Islamic Work Ethos through the Application of Morality and Islamic Law is an essential effort in shaping an ethical work environment based on Islamic principles. This research explores the role of morality and Islamic law in shaping an Islamic work ethos. Employing a qualitative approach, data were collected through interviews and document analysis. The findings indicate that a good understanding and application of morality can enhance productivity, work quality, and employee satisfaction. Conversely, a profound understanding of Islamic law provides a strong foundation for fair and responsible business practices.